Indigenous uses of medicinal plants in Tarikhet block of Kumaun Himalaya, India - Maurya, A. (2021)
Over 80% of the world population relies on vegetation for health care; more than 30% of the entire plant species are used for medicinal purposes. India displays large topography and various climatic conditions which accommodates more than 45,000 species. Uttarakhand state known as the ‘natural reservoir of India’ is in north-western Himalaya; it has 8000 vascular plants species, over 1748 of these are known for their therapeutic properties. In hilly areas of Uttarakhand, local communities still use the ethno-medicinal plants to cure various diseases and ailments. Although several researchers have conducted surveys across different areas of the Himalayan region, and to our knowledge, ethno-medicinal plants’ studies have not been conducted in Tarikhet block of Almora district, Uttarakhand. In this study, a total of 155 individuals of different age groups (20–93 years) with different socio-economic status (farmer, service man, ex-service man, businessman, housewives, students) participated. A total of 72 medicinal plant species were reported from which 31 were herbs, 20 trees, 15 shrubs and 6 were climbers belonging to 44 families used in the treatment of various ailments. Furthermore, we recorded that local people used various plant parts that is, leaves (35), fruit (15), root (10), whole plant (5), seed (6), bark (6) stem (4), rhizome (3) and others (4), to treat a wide range of health conditions. Thus, documenting the ethno-medicinal plants and for conservation is of the upmost important not only for cultural traditions and for biodiversity conservation. The study shows that locals have extensive ethnobotanical knowledge and are highly dependent on the forest for their livelihood. The valuable knowledge is anchored in cultural practices and orally transmitted from one generation to another; however, the loss is imminent as the new generation lacks the interest and the traditional ethnobotanical knowledge is unprotected.